PENDUGAAN MASA KADALUWARSA DENDENG LUMAT IKAN PATIN (Pangasius hypophthalmus) PADA KEMASAN ALUMINIUM FOIL - Elita Suryani Gultom; Dahlia '; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was to estimate the shelf life of catfish dendeng stored at room temperature (270C) and refrigerated temperature (50C). About 15 kg catfish weighing 600-800 gr each was obtained from a fish market in Pekanbaru. Two groups of dendeng prepared from catfish meat and the products were packed in aluminium foil and stored respectively at room temperature and refrigerated temperature for 49 days. Changes in the quality were analysed for peroxide value and moisture; and the shelf life was estimated by peroxide value and moisture using Arrhenius method. The results indicated that the shelf life of dendeng stored at room temperature and refrigerated temperature had a shelf life of 19,68 days and 26,69 days respectively. Peroxide value the dendeng stored at room temperature and refrigerated temperature at rejection was 21,17 and 18,82 meq/ 1000 g sample respectively; and moisture was 10,904% and 10,867% respectively.Key words : dendeng, shelf life temperature, arrhenius, peroxide, moisture